2013
DOI: 10.29173/cais568
|View full text |Cite
|
Sign up to set email alerts
|

Ontario Public Libraries, Accessibility, and Justice: A Capability Approach

Abstract: As public libraries are often considered levellers for the community, how are they addressing the needs of persons with disabilities in Ontario? This presentation details research on accessibility to persons with disabilities in Ontario public libraries through a capability perspective in light of the Access for Ontarians with Disabilities Act.Les bibliothèques publiques servent souvent d’indicateur communautaire. Comment répondent-elles donc aux besoins des personnes handicapées en Ontario? Cette communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Library users interviewed by Copeland (2011) noted a variety of accessibility challenges, including entrance steps with no ramp, heavy doors, narrow stacks, and the inaccessibility of washrooms. Hill's (2011) research confirmed some of the challenges noted by Copeland, while also outlining challenges to creating a moreaccessible built environment, like a lack of funding and other administrative impediments. In a broader study on accessibility, Lazar and Briggs (2015) noted builtenvironment issues with the Baltimore County Public Library branches, like inaccessible signage and a broken ramp railing.…”
Section: Public Library Literature On Accessibilitysupporting
confidence: 66%
See 3 more Smart Citations
“…Library users interviewed by Copeland (2011) noted a variety of accessibility challenges, including entrance steps with no ramp, heavy doors, narrow stacks, and the inaccessibility of washrooms. Hill's (2011) research confirmed some of the challenges noted by Copeland, while also outlining challenges to creating a moreaccessible built environment, like a lack of funding and other administrative impediments. In a broader study on accessibility, Lazar and Briggs (2015) noted builtenvironment issues with the Baltimore County Public Library branches, like inaccessible signage and a broken ramp railing.…”
Section: Public Library Literature On Accessibilitysupporting
confidence: 66%
“…It was initially expected that all codes would fall under traditional services and resources. The inclusion of information on the accessibility of the facility was an unexpected development, as previous research (Hill, 2011) found no information about the accessibility of the facility on library websites.…”
Section: Rq2: What Information On Accessibility Is Available?mentioning
confidence: 98%
See 2 more Smart Citations
“…This shift includes changing the language that lib raries use on web pages to focus on the community rather than the library, as Hill suggested. 16 Another example of the social model in practice would be using personcentered language such as "people with disabilities," rather than "dis abled people." This includes writing policy and training staff to talk about and to patrons with disabilities as patrons first, focusing on the disability only when it is substantively relev ant to the patron's specific need.…”
Section: Theoretical Frameworkmentioning
confidence: 99%